A Technical Efficiency Analysis of Hawaii's Aquaculture Industry. Issue 3 (June 2014) - Arita, Shawn; Leung, PingSun
Abstract This study examines the technical efficiency (TE) of aquaculture farms in Hawaii. Policy makers and industry participants interested in assessing the economic outlook of aquaculture production not only have to assess measures of profitability and financial health, but also measures of production efficiency. We estimate the TE of the state's aquafarms with a data envelopment analysis (DEA) model. Using data from the US Census of Agriculture, we examine TE measures of the population of Hawaii's aquafarms across different types of farms and over time. The results show that only 12% of the farms in 2007 may be classified as efficient, with a steady decline in efficiency over time. We find TE was related to the size of farm, full‐time farms were significantly more efficient than part‐time farms and that the average excess real inputs for land and labor have slightly fallen over time. The sub‐sector analysis revealed a strong variation of TE across different type of farms. With few farms operating on the frontier, the findings of this study suggest that the majority of the farms could improve their TE.